Incidencia y manejo de pacientes con diabetes mellitus tipo 2 atendidos en el hospital universitario de Motupe en el periodo comprendido desde enero a diciembre del 2009 - Castillo Jiménez, Jorge Alfredo (2011)
Investigation this letter thinks object it decides the incidence and handling of type diabetes patients 2 in the university hospital of Motupe in the period of the 2009. It deals with of a study of analytic, descriptive type, not experimental, retrospective. The universe constituted it all patients that it resorted to external consultation in the university hospital of Motupe of January to December of the 2009 for morbidity, the sample constitute it the patients with diagnosis of arterial hypertension. For the obtaining of data applied the sheet of collection, that it consists of data of affiliation and the main factors of risk, in any way whatever familiar age, sex, antecedents, diet and habits. With the data obtained decided an incidence of 0.95 % of the total of patients attended, the more frequent ages with this illness was 45-65-years with a 42.5 %, the sex I predominate went the feminine thing with a 90 %, in the factors of main risk were the antecedents of familiars with HTA in 87.5 %, absence of physical activity in 87 %, obesity in a 85 %, tobacco 7.5 %. The medicines more emploied went the Glibenclamida+metformina combination in a 50. This in turn permit conclude us that the change of habits and the practice drill helps a lot of to the treatment of the type diabetes 2 and also